How does this make you feel? A comparison of four affect induction procedures - Zhang, Xuan; Yu, Hui W.; Barrett, Lisa F. (Frontiers in Psychology, 2014)
Affect is a fundamental aspect of the human mind. An increasing number of experiments attempt to examine the influence of affect on other psychological phenomena. To accomplish this research, it is necessary to experimentally modify participants’ affective states. In the present experiment, we compared the effectiveness of four commonly used affect induction procedures. Participants were randomly assigned to either a pleasant or an unpleasant affect induction group, and then underwent four different affect induction procedures: (1) recall of an affectively salient event accompanied by affectively congruent music, (2) script-driven guided imagery, (3) viewing images while listening to affectively congruent music, and (4) posing affective facial actions, body postures, and vocal expressions. All four affect induction methods were successful in inducing both pleasant and unpleasant affective states. The combined image/music and recall/music procedures were most effective in enhancing pleasant affect, whereas the combined image/music procedure was most effective in enhancing unpleasant affect. Implications for the scientific study of affect are discussed.